2018
DOI: 10.1021/acsmedchemlett.8b00407
|View full text |Cite
|
Sign up to set email alerts
|

B-973, a Novel α7 nAChR Ago-PAM: Racemic and Asymmetric Synthesis, Electrophysiological Studies, and in Vivo Evaluation

Abstract: We report here the total synthesis of B-973 (five steps), a recently identified α7 nAChR ago-PAM, its enantiomeric resolution, and its electrophysiological characterization in Xenopus oocytes to identify (−)-B-973B as the bioactive enantiomer. The asymmetric synthesis of B-973B was accomplished in 99% ee, and X-ray crystallography studies revealed its absolute "S" stereochemistry. B-973B was effective in attenuating pain behavior and decreasing paw edema (formalin test), and its analgesic effects were mediated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 26 publications
1
12
0
Order By: Relevance
“…In this tight pocket stereochemical constraints appear to be very important. This was shown to be the case for three functionally diverse analogs in the TQS family, TQS itself (Stokes et al, 2019), the ago-PAM 4BP-TQS (Papke et al, 2014;Thakur et al, 2013), and the allosteric antagonist presented in this work, 2,3,5,6TMP-TQS, as well as for the structurally unrelated ago-PAM B-973B (Garai et al, 2018;Quadri et al, MOL#119958 2019). Additionally, a recently published study of a family of sulfonamide-containing PAMs showed that the stereochemical orientation of side groups around a critical central cyclopropyl ring determine whether enantiomers function as Type I or Type II a7 PAMs (Harvey et al, 2019;Wang et al, 2020).…”
Section: Discussionsupporting
confidence: 56%
“…In this tight pocket stereochemical constraints appear to be very important. This was shown to be the case for three functionally diverse analogs in the TQS family, TQS itself (Stokes et al, 2019), the ago-PAM 4BP-TQS (Papke et al, 2014;Thakur et al, 2013), and the allosteric antagonist presented in this work, 2,3,5,6TMP-TQS, as well as for the structurally unrelated ago-PAM B-973B (Garai et al, 2018;Quadri et al, MOL#119958 2019). Additionally, a recently published study of a family of sulfonamide-containing PAMs showed that the stereochemical orientation of side groups around a critical central cyclopropyl ring determine whether enantiomers function as Type I or Type II a7 PAMs (Harvey et al, 2019;Wang et al, 2020).…”
Section: Discussionsupporting
confidence: 56%
“…Acetylcholine chloride, atropine, and other chemicals were purchased from Sigma-Aldrich Chemical Company (St. Louis, MO), and (3aR,4S,9bS)-4-(4-bromophenyl)-3a,4,5,9b-tetrahydro-3H-cyclopenta [c]quinoline-8-sulfonamide (GAT107) (Kulkarni and Thakur, 2013;Thakur et al, 2013), 3-(3,4-difluorophenyl)-N-(1-(6-(4-(pyridin-2-yl) piperazin-1-yl)pyrazin-2-yl)ethyl)propenamide (Garai et al, 2018), and PNU-120596 (Williams et al, 2011a) were synthesized as described previously. Fresh ACh stock solutions were made in Ringer's solution each day of experimentation.…”
Section: Commercial Reagentsmentioning
confidence: 99%
“…Acetylcholine chloride (ACh), atropine, and other chemicals were purchased from Sigma-Aldrich Chemical Company (St. Louis, MO). GAT107 ((3aR,4S,9bS)-4-(4-bromophenyl)-3a,4,5,9btetrahydro-3H-cyclopenta[c]quinoline-8-sulfonamide) (Kulkarni and Thakur, 2013;Thakur et al, 2013), (Garai et al, 2018), and PNU-120596 (N-(5-Chloro-2,4-dimethoxyphenyl)-N'-(5-methyl-3-isoxazolyl)-urea) (Williams et al, 2011a) were synthesized as described previously. All compounds were confirmed by NMR to have a purity ≥ 95%.…”
Section: Reagentsmentioning
confidence: 99%
“…PAMs like PNU-120596 and TQS can increase a7 channel activity by two or more orders of magnitude. While PAMs like PNU-120596 and TQS require ACh, choline, or an exogenous agonist such as nicotine to produce channel activation, other compounds, for example GAT107 and B-973B, have been identified as allosteric agonist-positive allosteric modulators (ago-PAMs) and are capable of producing high levels of allosteric activation without additional orthosteric agonists (Garai et al, 2018;Horenstein et al, 2016). It has been a concern however, that such strong enhancement in the activity of a receptor with high calcium permeability may actually present a risk for the therapeutic development of PAMs and ago-PAMs due to calcium overload (Williams et al, 2011b).…”
Section: Introductionmentioning
confidence: 99%